Potential role of dengue virus, chikungunya virus and Zika virus in neurological diseases - Vieira, Marcelo Adriano da Cunha e Silva (Mem Inst Oswaldo Cruz, 2018)
This study showed that laboratory markers of recent infection by dengue, Zika or chikungunya arboviruses were detected in the biological samples of approximately one-third of patients with encephalitis, myelitis, encephalomyelitis or Guillain-Barré syndrome, in a surveillance programme in Piauí state, Brazil, between 2015-2016. Fever and myalgia had been associated with these cases. Since in non-tropical countries most infections or parainfectious diseases associated with the nervous system are attributed to herpesviruses, enteroviruses, and Campylobacter jejuni, the present findings indicate that in tropical countries, arboviruses may now play a more important role and reinforce the need for their surveillance and systematic investigation in the tropics.